PEMBELAJARAN BUDAYA JAWA DI SEKOLAH DASAR: STUDI KASUS DI SD ANTAWIRYA ISLAMIC JAVANESE SCHOOL - Nastiti, Syavina Putri; Widiana Rahayu, Dewi; Kasiyun, Suharmono; Akhwani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of Javanese cultural learning at SD Antawirya Islamic Javanese School, which integrates Islamic values with local wisdom. The problem addressed in this research is the declining implementation of local culture in education due to modernization and globalization, which affects students’ character and cultural identity. This research focuses on the learning process, the role of teachers and the school environment, as well as the challenges and strategies in maintaining Javanese culture. This study uses a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing, with triangulation applied to ensure data validity. The results show that Javanese cultural learning is integrated into daily school activities through the use of the Javanese language, the application of unggah-ungguh (etiquette), and culture-based learning programs such as the “Dolananku” module. Teachers and the school environment play a significant role as role models in instilling cultural and religious values. The main challenges include the influence of globalization and the lack of support from the external environment, particularly families. However, the implementation of this learning approach is proven to be effective in shaping students’ character to become polite, religious, and culturally grounded individuals.